(untitled) (British Journal of Global Ecology and Sustainable Development, 2024)
In this research work, the features of the international practice of real estate property valuation, in particular, the practice of using property value valuation services in making correct conclusions on real estate value growth and management decisions in developed and developing countries such as Great Britain, Italy, France and Germany, organization and control of valuation activities forms, international property valuation standards and their application in the valuation process, applied valuation principles and methods are described in detail. On the basis of international experiences of property value assessment in the Republic of Uzbekistan, proposals, recommendations and conclusions have been developed on the further improvement of the mechanisms of real estate value assessment activities.